2022
DOI: 10.1002/adma.202106826
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically Driven Polarization Flop and Strain‐Induced Curvature in Free‐Standing Ferroelectric Superlattices

Abstract: The combination of strain and electrostatic engineering in epitaxial heterostructures of ferroelectric oxides offers many possibilities for inducing new phases, complex polar topologies, and enhanced electrical properties. However, the dominant effect of substrate clamping can also limit the electromechanical response and often leaves electrostatics to play a secondary role. Releasing the mechanical constraint imposed by the substrate can not only dramatically alter the balance between elastic and electrostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…The flexoelectric polarization becomes so predominant at atomic scale that strain gradient engineering offers a new path toward manipulating electrical and mechanical behaviors in these strongly correlated two-dimensional materials as future potential building blocks in multifunctional flexible electronics 30 32 and nanomachines 2 . For example, the strong strain gradient within self-rolling heterostructures provides a powerful tool of flexoelectric polarization for designing novel energy harvesters and field-effect transistors 33 , 34 . Furthermore, the enhanced flexoelectric polarization opens a door for the application of intrinsic nonpolar materials in polarity-dependent electronics.…”
Section: Discussionmentioning
confidence: 99%
“…The flexoelectric polarization becomes so predominant at atomic scale that strain gradient engineering offers a new path toward manipulating electrical and mechanical behaviors in these strongly correlated two-dimensional materials as future potential building blocks in multifunctional flexible electronics 30 32 and nanomachines 2 . For example, the strong strain gradient within self-rolling heterostructures provides a powerful tool of flexoelectric polarization for designing novel energy harvesters and field-effect transistors 33 , 34 . Furthermore, the enhanced flexoelectric polarization opens a door for the application of intrinsic nonpolar materials in polarity-dependent electronics.…”
Section: Discussionmentioning
confidence: 99%
“…[ 65 ] Additionally, Li et al observed a radical transformation of the polarization direction in PbTiO 3 /STO superlattice with a SRO bottom electrode when released from its substrate. [ 126 ] Interestingly, the variation of the polarization direction in the superlattice drove the membrane to curl up into microtubes, in order to minimize the overall elastic energy. These results show that the suppression of the mechanical interaction with the substrates may influence the polarization dynamics of ferroelectric perovskite oxides.…”
Section: Emerging Functionalities In Freestanding Perovskite Thin Filmsmentioning
confidence: 99%
“…Being free from substrate clamping, such mechanical boundary conditions can be affected by electrostatic considerations, such as depolarizing fields. This was observed in PbTiO 3 /SrTiO 3 superlattices, where the strain-induced out-of-plane polarization in the epitaxial films is destabilized once the superlattice is released from the substrate, leading to in-plane polarization and flux-closure domains that eliminate the depolarizing field and causes large lattice mismatch with the bottom SrRuO 3 electrode and the curling of the membranes into microscopic rolls [165]. X-ray diffraction and cross-sectional TEM studies reveal the distribution of ferroelastic domains across the thickness of the superlattice rolls, as a mechanism for accommodating the curvature (figure 5(b)).…”
Section: Superelastic Deformation In Ferroelastic-fe Membranesmentioning
confidence: 95%